Determination of the distribution of infectious viruses in aerosol particles using water-based condensational growth technology and a bacteriophage MS2 model. Issue 5 (4th May 2019) - Pan, Maohua; Carol, Leah; Lednicky, John A.; Eiguren-Fernandez, Arantzazu; Hering, Susanne; Fan, Z. Hugh; Wu, Chang-Yu
Abstract: Inhalation of aerosols containing pathogenic viruses can result in morbidity, in some cases leading to mortality. The objective of this study was to develop a model for assessing how infectious viruses might distribute in airborne particles using bacteriophage MS2 as a surrogate for human viruses. Particle deposition in the respiratory system is size-dependent, and small virus-containing particles can be inhaled deeply into the lower lungs, potentially leading to more severe respiratory disease manifestations. Laboratory-generated virus-containing particles were size-selected by a differential mobility analyzer and then collected by the newly introduced Super-Efficient Sampler for Influenza Virus. The number of infectious and total viruses per particle as a function of particle size varied with the spraying medium: it approximated a cubic exponential value scaling for deionized (DI) water, a quartic exponential value for artificial saliva (AS), and between quadratic and cubic exponential value for beef extract solution (BES). The survivability of MS2 did not change significantly with particle size for DI water and BES, while that for AS was maximum at 120 nm. Viruses could be homogeneously distributed or aggregated inside or on the surface of the particles, depending on the composition of the spraying medium. Copyright © 2019 American Association for Aerosol Research